Obesity in children - Šimková, Simona (Jihočeská univerzita v Českých Budějovicích, Zdravotně sociální fakulta, 2020)
Obesity is a non-infectious chronic illness which occurs from childhood. Its incidence is caused by many factors (one of them is genetic predisposition). However, the most significant and governable part is lifestyle. Particularly problematic is the fact that 80% of obese children and adolescents remain obese in adulthood. The goal of this article is to inform experts and the wider public about the significant risk factors regarding overweight and obese children. There can be complications caused by obesity, such as diabetes mellitus, hypertension or dyslipidemia. The most important thing is prevention. In today’s Czech Republic, the number of overweight children and adolescents is at a standstill but it is not dropping. Significant obesity risk factors include energy-rich diet, excessive intake of simple sugars, sedentary lifestyle, hours spent watching television and insufficient time spent outdoors. The illness is multifactorial, thus the treatment is multidisciplinary. It is more important to prevent this illness than rely on the possibilities of therapy.
Keywords: Activity; Children; Health complications; Nutrition; Obesity; Overweight; Risk factors